O RELACIONAMENTO SOCIAL-ECONÔMICO-GERENCIAL INTERFIRMAS: O CASO DO CLUSTER DA INDÚSTRIA DO VESTUaRIO NO MUNICaPIO DE COLATINA (ES) - Garcia, Fernando Coutinho; Dadalto, Maria Cristina (Revista Economia Ensaios, 2008)
ResumoTrês modelos de produção sobressaíram no decorrer do século XX: o modelo fordista, o modelo de coordenaçãoe o modelo comunitário. A dinâmica de cada um desses modelos, por outro lado, está intrinsecamenterelacionada à sociedade que os suscitou. Transpostos para o mundo das organizações, esses valores revelam-sepor meio do relacionamento interfirmas. Neste artigo se analisa a dinâmica de relacionamento interfirmas noaglomerado da indústria do vestuário do município de Colatina, no Espírito Santo. A análise tem como principalreferência a sistematização das principais características do modelo comunitário de produção dos DistritosIndustriais (DIÂ´s) italianos.AbstractThe 20th century was a period of deep social, economical, technological and organizational alterations.Underlying to the understanding of those transformations is the comprehension of the production model and thesocial regulation that permeate some society in its development process. Then, three production models stoodout in elapsing of this century: the Ford model, the coordination model and the community model. The dynamicsof each one of those models is inherently related to the society that raised them. So, we can relate the Fordmodel to the American consumer society, the coordination model to the Japanese hierarchical culture and thecommunity model to the cooperation and reciprocity nets of the north of Italy. The evolution of each one ofthose models offers a certain answer to the organizational development, which also corresponds to specificperiods in the relationship between economy and production. Paradoxically, in the current world, whichdemands fast answers, contacts seemingly superficial and flexibility, the Japanese and Italian production